2022
DOI: 10.47654/v26y2022i1p102-127
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Impact of COVID-19 Epidemic on China Exports using Different Time Series Models

Abstract: Purpose: The primary objective of this paper is to identify the best forecasting model for China exports, especially during the spread of the COVID-19 pandemic.Methodology: We used the data of China exports to the United States and different economic regions from January 2014 to January 2021 to compare models using various criteria and selected the best exports forecast model. The hybrid model is employed to conduct the analysis.The combination of the hybrid model consists of six different models: ARIMA, ETS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…They concluded that by using the appropriate methods that are suitable to the data, one can achieve consistent results in modelling and predicting any series of an epidemic. For more epidemic hybrid time series forecasting, see, for example, 34 42 .…”
Section: Literature Reviews and Related Workmentioning
confidence: 99%
“…They concluded that by using the appropriate methods that are suitable to the data, one can achieve consistent results in modelling and predicting any series of an epidemic. For more epidemic hybrid time series forecasting, see, for example, 34 42 .…”
Section: Literature Reviews and Related Workmentioning
confidence: 99%
“…The root mean square error (RMSE), mean absolute error (MAE), and mean percentage errors (MAPE) are used to evaluate the predictive performance of the models. To the best of our knowledge, these are the most common measures used to assess the accuracy of nonlinear and hybrid models (Ravazzolo et al 2020;Safi et al 2022). Table 2 shows the accuracy of the prediction of ARIMA-NNAR model over the benchmark models when the 518 observed data are compared with the prediction data.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, COVID-19 has negatively affected the exportations. For example, Safi et al (2022), showed how the COVID-19 pandemic has disrupted the flow of goods that China exports to other parts of the world and forecast the China exports during the COVID-19 pandemic using seven different forecasting models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the emergence of the Global Financial Crisis, a large body of literature exists to discuss the detection of bubbles. (Safi et al, 2022;Foroni et al, 2020). In relation to the investors' behavior, Bourdeau-Brien and Kryzanowski (2020) found that "natural disasters cause a statistically and economically significant increase in risk aversion at the local level", Brown et al (2018) show that "being struck by an extreme event substantially changed individuals' risk perceptions as well as their beliefs about the frequency and magnitude of future shocks", and Sun et al…”
Section: Literature Reviewmentioning
confidence: 99%